BLENDER 3D UNTUK PENDIDIKAN ANIMASI - Mochamad Faizal Rochman (Institut Seni Indonesia Yogyakarta, 2012)
Animation has become one of the pillars of the creative industries that have been set by thegovernment. Animation is a major industry in addition to requiring a lot of human resources also requiresgreater availability of funds. The role of academia to create and educate human resources are necessaryto meet the demands of the growing animation industry. Constraints in advancing educational animatedclassic one is the issue of availability of funds. Because the animation industry is an industry that requiresthe availability of hardware and software are very expensive.This paper aims to ensure that the use of Free Open Source Software (FOSS) Blender 3D is verysuitable to be applied in the world of education as an introduction to the study of three-dimensionalanimation.